Gene drive systems for insect disease vectors - Sinkins, Steven P.; Gould, Fred (Nature reviews. Genetics, 2006)
Key Points Advances in the molecular biology of insect disease vectors, particularly mosquitoes, have made it possible to express constructs that can block the transmission of pathogens such as Plasmodium in model systems. Methods for spreading constructs through natural populations are now much needed. Various transposable elements (TEs) are common in insects and in their autonomous form can increase their germline copy number, thereby providing a potential transgene drive mechanism. More needs to be known about the rates of transposition of TEs in target species, with and without inserts, and the stability of inserted genes. Homing endonuclease genes (HEGs) encode site-specific endonucleases and their copy number can increase through homologous repair. They have not been found in animals; research is needed to determine whether operational systems could be produced in insects. Various meiotic drive mechanisms (with unequal representation of alleles at meiotic segregation) are found in insects; it might be possible to engineer artificial versions for transgene drive, particularly if naturally occurring mechanisms can be better understood. Engineered underdominance has been proposed as a gene-spreading system, using combinations of lethal genes and trans -acting suppressors. The release frequencies that are required would be comparatively high with this system. The inherited endosymbiotic bacterium Wolbachia is able to spread through populations using cytoplasmic incompatibility. It could be used in disease control if it could be transformed to express and secrete gene products in relevant tissues, or if a virulent strain could reduce host lifespan in target species. Effective gene drive systems for spreading genes that can block the transmission of insect-borne pathogens are much needed. Naturally occurring selfish genetic elements have enormous potential that can be exploited to control of some of the world's most devastating diseases. The elegant mechanisms by which naturally occurring selfish genetic elements, such as transposable elements, meiotic drive genes, homing endonuclease genes and Wolbachia , spread at the expense of their hosts provide some of the most fascinating and remarkable subjects in evolutionary genetics. These elements also have enormous untapped potential to be used in the control of some of the world's most devastating diseases. Effective gene drive systems for spreading genes that can block the transmission of insect-borne pathogens are much needed. Here we explore the potential of natural gene drive systems and discuss the artificial constructs that could be envisaged for this purpose.